Is there a relationship between cardiorespiratory fitness and executive performance as function of mental workload in young adults? - Agbangla, Nounagnon Frutueux; Pater Maire, Marion; Maillot, Pauline; Vitiello, Damien (Frontiers in Psychology, 2022)
In the current study, we have decided to investigate the relationship between cardiorespiratory fitness and executive functions in young adults as a function of mental workload. To achieve our objectives, we have solicited 29 young adults (18-25 years; 12 women) who have first realized the Random Number Generation (RNG) task with two levels of complexity. After each level of complexity, the participants were asked to report on their perceived difficulty. Secondly, participants performed the RABIT® test, during which oxygen consumption was measured through the Metamax3B-R2. The results showed that executive performance and perceived difficulty deteriorate with increasing task complexity. Additionally, oxygen consumption increased significantly to reach a peak during the hardest phase of the RABIT® test. Finally, as in previous studies, we could not observe a correlation between cardiorespiratory fitness and executive functions. Our findings support the lack of a direct relationship between cardiorespiratory fitness and executive functions.